EXPERIMENTAL AND THEORETICAL ANALYSIS OF SOLVENTS EFFECT ON A DERİVATİVE OF CARBOTHIOAMIDE - Koparır, Pelin (Niyazi BULUT, 2024)
The titled molecules is an optically pure anti-cancer agent and also plays a vital role as an important staritng material for developing medicines that can cure many disease. Synthesis of carbothiomide is a subject of deep chemical and biochemical research due to its medicinal value and can also use as a starting material for many important compounds. In this work 2,2'-[(2R,3R)-2,3-dihydroxy-1,4-dioxobutane-1,4-dıyl]bis(N-P-tolyhydrazine-1-carbothioamıde was synthesized experimentally in the laboatory and then characterized. The structure was later designed and optimized by Gaussian 09 package using ab initio method. To obtain the minimum energy of the titled structure, many basis set in density functional theory (DFT) and Hatree-Fock (HF) were used in geometry optimization. The molecule was characterized using spectroscopic methods such as 1H-NMR, 13C-NMR, FT-IR to determine the molecular dynamics as well as their optical and electrical properties. The energy difference between the HOMO and LUMO was computed. The homo and homo was found to be -0.15064 and -0.035472 eV respectively. The bandgap was also found to be -3.133 eV. The optimized titled structure then undergoes spectroscopic calculations to determined the theoretical spectroscopic parameters. A comparison was also studied between the theoretical and experimental datas. Finally, the effect of polar and non-polar solvent ( DMSO and CCl4) on the optimized titled compound is analysed. It was found that the bandgap respond to the addition of solvent due to the involvement of the molecules in the solvent. The polar solvent has highest bandgap values due to the fact that the titled molecule is polar and its molecules can interact more easily with polar solvent that non-polar solvent. This result indicate that polar solvent can be use to increase the effectiveness of the titled molecule in terms of medicinal value.
Keywords: Molecular Imaging; Moleküler Görüntüleme